Haloperidol, but not olanzapine, may affect expression of PER1 and CRY1 genes in human glioblastoma cell line. Issue 6 (1st November 2016) - Mokros, Łukasz; Karbownik, Michał Seweryn; Nowakowska-Domagała, Katarzyna; Szemraj, Janusz; Wieteska, Łukasz; Woźniak, Karol; Witusik, Andrzej; Antczak, Adam; Pietras, Tadeusz
Abstract: Background : There is barely any evidence of antipsychotic drugs affecting the molecular clockwork in human, yet it is suggested that clock genes are associated with dopaminergic transmission, i.e. the main target of this therapeutics. We decided to verify if haloperidol and olanzapine affect expression of CLOCK, BMAL1, PER1 and CRY1 in a human central nervous system cell line model.Methods : U-87MG human glioblastoma cell line was used as an experimental model. The cells were incubated with or without haloperidol and olanzapine in the concentration of 5 and 20 μM for 24 h. Real-time quantitative polymerase chain reaction with the Δ C T analysis was used to examine the effect of haloperidol and olanzapine on the mRNA expression of the genes.Results : At 5 μM, haloperidol decreased expression of CRY1 almost 20-fold. There was nearly a 1.5-fold increase in expression of PER1 . Considering the 20 μM haloperidol concentration and both olanzapine concentrations, no other statistically significant effect was observed.Conclusions : At certain concentration, haloperidol seems to affect expression of particular clock genes in a human central nervous system cell line model, yet mechanism underlying this phenomenon remains elusive.